Pembangunan Desa Wisata Senaru dalam Konsep Public Private Partnership - Septiadi Septiadi Septiadi; Siti Atika Rahmi; Muhammad Aprian Jailani (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
This study aims to provide knowledge about how partnerships are carried out between the government and the private sector in the Development of Senaru Tourism Village. This research uses a descriptive approach with a qualitative approach method. Data collection techniques by conducting interviews by preparing several questions to informants, namely the Senaru Village government and private parties. Second, observation by making direct observations by researchers in Senaru Tourism Village. Third, Documentation with shooting in the field. The development of Senaru Tourism Village uses the concept of partnership where cooperation between the government and the private sector uses the approach of